What's up? Thoughts on choosing a career in high school (Training and Practice : Journal of Educational Sciences, 2020)
In a truly exciting age, when a child becomes a young adult, he or she also has to cope with the first serious decision-making. The question is from where and with what information and how consciously you do this. To what extent and in what way social expectations, the family microenvironment and peer groups influence, help, or even hinder the student in making a decision. In my study, I present the problems and the helping factors of adolescence, which we must not overlook when choosing a career. In my research, I am looking for the answer to how consciously and thoughtfully students from the 8th grade to the 9th grade of vocational education choose a profession, a secondary school.